Late-stage C–H amination of abietane diterpenoids - Lapuh, María Ivana (2019)
This study aims at highlighting the synthetic versatility of the rhodium-catalyzed C-H amination reactions using iodine(iii) oxidants for the late-stage functionalization of natural products. Inter-and intramolecular nitrene insertions have been performed from various abietane diterpenoids, leading to the amination of the C-3, C-6, C-7, C-11 and C-15 positions. Ca. 20 aminated compounds have been isolated with yields of up to 86% and high levels of regio-, chemo-and stereoselectivities.